Evolution and Diversity of the Antimicrobial Resistance Associated Mobilome in Streptococcus suis: A Probable Mobile Genetic Elements Reservoir for Other Streptococci - Huang, Jinhu; Ma, Jiale; Shang, Kexin; Hu, Xiao; Liang, Yuan; Li, Daiwei; Wu, Zuowei; Dai, Lei; Chen, Li; Wang, Liping (Frontiers in Cellular and Infection Microbiology, 2016)
Streptococcus suis is a previously neglected, newly emerging multidrug-resistant zoonotic pathogen. Mobile genetic elements (MGEs) play a key role in intra- and interspecies horizontal transfer of antimicrobial resistance (AMR) determinants. Although previous studies showed the presence of several MGEs, a comprehensive analysis of AMR-associated mobilome as well as their interaction and evolution has not been performed. In this study, we presented the AMR-associated mobilome and their insertion hotspots in S. suis. Integrative conjugative elements (ICEs), prophages and tandem MGEs were located at different insertion sites, while 86% of the AMR-associated MGEs were inserted at rplL and rum loci. Comprehensive analysis of insertions at rplL and rum loci among four pathogenic Streptococcus species (Streptococcus agalactiae, Streptococcus pneumoniae, Streptococcus pyogenes, and S. suis) revealed the existence of different groups of MGEs, including Tn5252, ICESp1108, and TnGBS2 groups ICEs, Φm46.1 group prophage, ICE_ICE and ICE_prophage tandem MGEs. Comparative ICE genomics of ICESa2603 family revealed that module exchange and acquisition/deletion were the main mechanisms in MGEs’ expansion and evolution. Furthermore, the observation of tandem MGEs reflected a novel mechanism for MGE diversity. Moreover, an in vitro competition assay showed no visible fitness cost was observed between different MGE-carrying isolates and a conjugation assay revealed the transferability of ICESa2603 family of ICEs. Our statistics further indicated that the prevalence and diversity of MGEs in S. suis is much greater than in other three species which prompted our hypothesis that S. suis is probably a MGEs reservoir for other streptococci. In conclusion, our results showed that acquisition of MGEs confers S. suis not only its capability as a multidrug resistance pathogen, but also represents a paradigm to study the modular evolution and matryoshkas of MGEs.